2022
DOI: 10.2196/34061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mHealth Interventions on Improving Antenatal Care Visits and Skilled Delivery Care in Low- and Middle-Income Countries: Systematic Review and Meta-analysis

Abstract: Background The poor coverage of essential maternal services, such as antenatal care (ANC) and skilled delivery care utilization, accounts for higher maternal and infant mortality in low- and middle-income countries (LMICs). Although mobile health (mHealth) interventions could potentially improve the service utilization in resource-limited settings, their effectiveness remains unclear. Objective This review aimed to summarize the effect of mHealth interv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…22 A crucial aspect of our study is that it evaluates the efficacy of a mhealth intervention on ANC utilization based on the most recent WHO recommendation and focuses on a voice message-based intervention that has seldom been evaluated. 13 However, a few restrictions must be considered when interpreting our results. First, we took a pragmatic approach by randomizing PHCs instead of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 A crucial aspect of our study is that it evaluates the efficacy of a mhealth intervention on ANC utilization based on the most recent WHO recommendation and focuses on a voice message-based intervention that has seldom been evaluated. 13 However, a few restrictions must be considered when interpreting our results. First, we took a pragmatic approach by randomizing PHCs instead of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mobile devices have been utilized to enhance the utilization of maternal health care in low-and middle-income countries (LMICs), particularly to improve patient education and appointment adherence, disease self-management, and remote patient monitoring. 12,13 In particular, research has demonstrated that successful communication and interaction between skilled health workers (SHP) and pregnant women via simple short message systems (SMS) increased the utilization of maternity services. 14−16 Indeed, studies have demonstrated a correlation between mobile health and the utilization of maternal health services, particularly ANC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Globally, most pregnant women have access to prenatal care visits with a skilled health professional (i.e., a physician, nurse, or midwife), but only 65% receive WHO-recommended four visits during pregnancy, and this number is even worse considering only low-income countries. 9 Regular prenatal care guarantees close contact between pregnant women and the health system. The practices during visits are essential to early suspicion and diagnosis of many insults, including hypertensive disorders.…”
Section: Prenatal Carementioning
confidence: 99%
“…Once hypertension is identified, medication should be prescribed, and its availability is another issue that health professionals must deal with. 9,10 During prenatal care, it is possible to recognize a pregnant woman at high-risk of developing pre-eclampsia, and considering the social and economic context of LMICs, clinical evaluation is the strategy to be implemented for this purpose. Although many efforts have been made towards universal screening between 11 and 13 weeks of pregnancy, the algorithm applied usually involves maternal characteristics, evaluation of mean arterial blood pressure, uterine artery Doppler, and serum levels of placental growth factor and pregnancy-associated pregnancy protein-A.…”
Section: Prenatal Carementioning
confidence: 99%